Continental Portuguese Territory Flood Susceptibility Index : contribution to a vulnerability index - Jacinto, Rita (2017)
This work defines a national flood susceptibility index for the Portuguese continental territory, by proposing the aggregation of different variables which represent natural conditions for permeability, runoff and accumulation. This index is part of the national vulnerability index developed in the scope of Flood Maps in Climate Change Scenarios (CIRAC) project, supported by the Portuguese Association of Insurers (APS). This approach expands on previous works by trying to bridge the gap between different flood mechanisms (e.g. progressive and flash floods) occurring at different spatial scales in the Portuguese territory through (a) selecting homogeneously processed data sets and (b) aggregating their values to better translate the spatially continuous and cumulative influence in floods at multiple spatial scales. Results show a good ability to capture, in the higher susceptibility classes, different flood types: fluvial floods and flash floods. Lower values are usually related to mountainous areas, low water accumulation potential and more permeable soils. Validation with independent flood data sets confirmed these index characteristics, although some overestimation can be seen in the southern region of Alentejo where, due to a dense hydrographic network and an overall low slope, floods are not as frequent as a result of lower precipitation mean values. Future work will focus on (i) including extreme precipitation data sets to represent the triggering factor, (ii) improving representation of smaller and stepper basins, (iii) optimizing variable weight definition process and (iii) developing more robust independent flood validation data sets.